Hybridisation between dingoes and domestic dogs in proximity to Indigenous communities in northern Australia. Issue 9 (9th June 2021) - Gabriele‐Rivet, V; Brookes, VJ; Stephens, D; Arsenault, J; Ward, MP
Abstract : In northern Australia, wild dog populations potentially interact with domestic dogs from remote communities, which would create opportunities for disease transmission at the wild–domestic interface. An example is rabies, in the event of an incursion into northern Australia. However, the likelihood of such wild–domestic interactions is ambiguous. Hybridisation analyses based on 23 microsatellite DNA markers were performed on canine‐origin scats collected in bushland areas around remote Indigenous communities in the Northern Peninsula Area, Queensland. Sufficient DNA was extracted from 6 of 41 scats to assess the percentage of dingo purity. These scats most likely originated from two 'pure' domestic dogs (0% dingo purity), one hybrid (20% dingo purity) and three 'pure' dingoes (92%–98% dingo purity). The two domestic dog samples were collected in the vicinity of communities. The location of two of the dingo‐origin samples provides genetic evidence that dingoes are present in areas close to the communities. The availability of anthropogenic food resources likely creates opportunities for interactions with domestic dogs in the region. The hybrid sample demonstrates the occurrence of antecedent contacts between both populations by means of mating and supports the likelihood of a spatio‐temporal overlap at the wild–domestic interface. This represents the first genetic survey involving a wild dog population of equatorial northern Queensland, with evidence of dingo purity. Our results have implications for potential disease transmission within a priority area for biosecurity in northern Australia.